2013
DOI: 10.1093/fampra/cms087
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing cancer in the bush: a mixed-methods study of symptom appraisal and help-seeking behaviour in people with cancer from rural Western Australia

Abstract: Longer symptom appraisal was observed for colorectal cancer. Participants defined core characteristics of rural Australians as optimism, stoicism and machismo. These features, as well as access to health care, contribute to later presentation of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
160
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(173 citation statements)
references
References 25 publications
10
160
3
Order By: Relevance
“…Such ruralurban differences may be driven by social cultural differences in health-seeking behaviour, where the most remote rural patients may be displaying stoicism when seeking help. 3,4,8,26 This may be supported by studies from northern Scotland that found rural patients were more likely to present later, had lower expectations of health care, and may pursue their care less tenaciously.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Such ruralurban differences may be driven by social cultural differences in health-seeking behaviour, where the most remote rural patients may be displaying stoicism when seeking help. 3,4,8,26 This may be supported by studies from northern Scotland that found rural patients were more likely to present later, had lower expectations of health care, and may pursue their care less tenaciously.…”
mentioning
confidence: 90%
“…3 First, rural populations may be impacted disproportionately by financial constraints and poor accessibility, compounded by the long distances travelled to obtain primary and secondary health care. 4 For example, longer distance to health services has been associated with fewer in-patient admissions, 5 with poorer uptake of cancer diagnosis and treatment, 1,6,7 and with lower survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Over two centuries have passed since the British arrived in Australia or as sometimes referred to as the 'invasion'. 40 Over this time Indigenous Australians were forcibly removed from their lands and separated from their families which resulted in the loss of traditional ways and values. 13,23 Colonisation is seen to have caused most of the adversity faced by Indigenous Australians.…”
Section: The Historical Influencementioning
confidence: 99%
“…10 Therefore, we should be aiming to prevent lung cancer by raising awareness of risk factors and increasing patient support to facilitate early diagnosis and treatment. 40 Well rounded health promotion or prevention activities considerate of culture and language can help mitigate fatalistic attitudes and reluctance to seek treatments. 11 Health professionals who have an awareness and understanding of Indigenous Australians' culture are better equipped to provide information on cancer in a culturally sensitive, relevant manner.…”
Section: Culture and Health Decisionsmentioning
confidence: 99%